2016
DOI: 10.1021/acs.chemmater.6b03379
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Naphthalenediimide-Based Hole Semiconducting Polymer with Vinylene Linkers between Donor and Acceptor Units

Abstract: We demonstrate a new method to reverse the polarity and charge transport behavior of naphthalenediimide (NDI)-based copolymers by inserting a vinylene linker between the donor and acceptor units. The vinylene linkers minimize the intrinsic steric congestion between the NDI and thiophene moieties to prompt backbone planarity. The polymers with vinylene linkers exhibit electron n-channel transport characteristics under vacuum, similar to the benchmark polymer, P(NDI2OD-T2). To our surprise, when the polymers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 75 publications
(112 reference statements)
0
39
0
Order By: Relevance
“…[15a] However,a ll reported BTI-based polymers were synthesized exclusively from dibrominated BTI monomer,which could limit polymer synthetic routes,m olecular weights,a nd structures.I tw as found that Yamamoto,Ullman, and Stille couplings could also be applied for the synthesis of A-A type polymers,h owever the resulting polymers generally showed low number-average molecular weight (M n )a nd (or) structural defects,w hich led to OTFT performance variation over aw ide range. [15a, 21a,b, 22] Marder et al first reported distannylated electron-deficient NDIs, [23] which were then widely used in the development of n-type oligomers and A-A copolymers, [24,25] showing low-lying FMO levels.W hen applied in OTFTs,p olymers PSN-NDI and PBBT-NDI [25b] (Figure 1b)y ielded moderate m e,OTFT values of 0.0011 and 0.039 cm 2 V À1 s À1 ,r espectively, owing to their twisted backbone,a nd the devices based on PBBT-NDI exhibited long-term stability.T oa lleviate steric hindrance associated with NDI, vinylene linker was attached and an ovel NDI monomer containing two (tributylstannyl)vinyl groups was reported by Heeney [26] and Briseno, [27] independently.T he bis(tributylstannyl)vinyl NDI enables development of high-performance unipolar n-type polymers. Polymer P3 featured planar backbone and the OTFTs showed an excellent m e,OTFT up to 3.87 cm 2 V À1 s À1 with ar emarkable stability in air,a nd P4-based devices exhibited af urther increased m e,OTFT of 7.16 cm 2 V À1 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…[15a] However,a ll reported BTI-based polymers were synthesized exclusively from dibrominated BTI monomer,which could limit polymer synthetic routes,m olecular weights,a nd structures.I tw as found that Yamamoto,Ullman, and Stille couplings could also be applied for the synthesis of A-A type polymers,h owever the resulting polymers generally showed low number-average molecular weight (M n )a nd (or) structural defects,w hich led to OTFT performance variation over aw ide range. [15a, 21a,b, 22] Marder et al first reported distannylated electron-deficient NDIs, [23] which were then widely used in the development of n-type oligomers and A-A copolymers, [24,25] showing low-lying FMO levels.W hen applied in OTFTs,p olymers PSN-NDI and PBBT-NDI [25b] (Figure 1b)y ielded moderate m e,OTFT values of 0.0011 and 0.039 cm 2 V À1 s À1 ,r espectively, owing to their twisted backbone,a nd the devices based on PBBT-NDI exhibited long-term stability.T oa lleviate steric hindrance associated with NDI, vinylene linker was attached and an ovel NDI monomer containing two (tributylstannyl)vinyl groups was reported by Heeney [26] and Briseno, [27] independently.T he bis(tributylstannyl)vinyl NDI enables development of high-performance unipolar n-type polymers. Polymer P3 featured planar backbone and the OTFTs showed an excellent m e,OTFT up to 3.87 cm 2 V À1 s À1 with ar emarkable stability in air,a nd P4-based devices exhibited af urther increased m e,OTFT of 7.16 cm 2 V À1 s À1 .…”
Section: Introductionmentioning
confidence: 99%
“…When applied in OTFTs, polymers PSN‐NDI and PBBT‐NDI (Figure b) yielded moderate μ e,OTFT values of 0.0011 and 0.039 cm 2 V −1 s −1 , respectively, owing to their twisted backbone, and the devices based on PBBT‐NDI exhibited long‐term stability. To alleviate steric hindrance associated with NDI, vinylene linker was attached and a novel NDI monomer containing two (tributylstannyl)vinyl groups was reported by Heeney and Briseno, independently. The bis(tributylstannyl)vinyl NDI enables development of high‐performance unipolar n‐type polymers.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been proved to be an effective strategy to tune the thin film morphology, which strongly influences the charge separation and charge transport. On the other hand, the material properties can be also tuned via modification the π‐conjugated backbone that has great impact on the electronic structure, such as ionization potential, electron affinity, and electronic delocalization . In recent years, different strategies have been developed to a fine‐tuning energy level through the careful combinations of different subunits or the incorporation of electron‐donating/electron‐withdrawing substituents into backbones .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the material properties can be also tuned via modification the p-conjugated backbone that has great impact on the electronic structure, such as ionization potential, electron affinity,a nd elec-tronic delocalization. [17][18][19][20][21][22] In recenty ears, different strategies have been developed to af ine-tuning energy level through the careful combinationsofdifferent subunits or the incorporation of electron-donating/electron-withdrawings ubstituents into backbones. [23][24][25][26][27] For example, fluorine atom has been widely incorporated into polymer backbones that significantly influence the energy level, backbonep lanarity,s olubility,a nd crystallization.…”
Section: Introductionmentioning
confidence: 99%